Stainless steel, production method thereof and electrolytic copper cathode plate
The introduction of Co and Cu in a tailored stainless steel composition for electric copper cathode production addresses corrosion and adhesion issues, enhancing cathode quality and production efficiency while reducing costs.
Patent Information
- Application Number
- CN202411738730.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-18
AI Technical Summary
Current electric copper cathode production faces issues with corrosion of cathode plates due to the presence of impurities, leading to reduced cathode quality, increased production costs, and decreased efficiency, as existing materials like 304 and 316L stainless steel do not adequately address corrosion and adhesion problems in electrochemical environments.
A specific composition of stainless steel with controlled chemical composition, including added Co and Cu elements, is developed to enhance corrosion resistance, adhesion properties, and processing characteristics, specifically tailored for electric copper cathode production, utilizing a modified production process to achieve improved surface roughness and mechanical properties.
The new stainless steel composition significantly improves the cathode's corrosion resistance, adhesion, and production efficiency, extending its lifespan and reducing production costs while maintaining high copper purity, thus addressing the limitations of existing materials and processes.
Smart Images

Figure CN119640131A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stainless steel manufacturing, and in particular to stainless steel and a production method thereof, and an electrolytic copper cathode plate. Background Art
[0002] In nature, copper metal rarely exists as a single substance, but usually exists in the form of compounds or metal paragenesis, accompanied by many other metals, such as gold, silver, nickel, molybdenum, lead, etc. In the application field of copper, copper materials containing associated elements often cause product performance degradation, abnormal equipment damage, abnormal conductivity, etc. With the continuous development of science and technology, all walks of life have higher and higher requirements for the purity of copper. For example, the standard "GB / T467-2010 Cathode Copper" stipulates that the main component copper content of 2# standard copper (Cu-CATH-3) is not less than 99.9%. However, the refined copper produced by pyro-refining generally contains 99.2%-99.7% copper, and inevitably contains 0.3-0.8% impurity elements. In addition to reducing the quality of copper, these impurity elements usually contain a variety of precious metals. Therefore, electrolytic refining, removing impurities, increasing the copper content to more than 99.9%, and recovering precious metals have become an indispensable processing link for producing high-quality copper.
[0003] As for the conventional electrolytic copper cathode plates in the current market, due to the presence of certain corrosiveness in the mixed solution of sulfuric acid and copper sulfate, in order to avoid abnormal corrosion of the cathode plate, the cathode plate is required to have a certain degree of corrosion resistance. Many manufacturers generally use 304 stainless steel, 321 stainless steel, 316L stainless steel and even expensive titanium plates as materials for manufacturing electrolytic copper cathode plates. Although 304 stainless steel, 321 stainless steel, and 316L stainless steel can improve the current density problem to a certain extent, corrosion cannot be avoided. The use of expensive titanium plates as electrolytic copper cathode plates, although the corrosion problem is avoided, requires the production of primary sheets before use due to the high resistance of the titanium surface oxide layer, which greatly affects the production efficiency of the enterprise. Moreover, after a certain amount of cathode copper is deposited on the cathode plate, either the adhesion is insufficient and it peels off prematurely, causing the production line circuit to short-circuit and stop production, or the adhesion is too strong, causing the cathode plate to deform and be damaged during mechanical peeling.
[0004] In the field of copper electrolytic refining technology, many existing technologies and research often focus on innovations in the shape and structure of cathode plates, while there is less research on material performance optimization innovation and industrial production of cathode plates.
[0005] Although the public invention patent CN101166850A has made some research on the selection of steel types and surface properties of the cathode plate, the 304 stainless steel and duplex stainless steel mentioned in the patent both need to be plated to achieve the roughness required for adhesion, and 304 stainless steel cannot resist corrosion from sulfuric acid and copper sulfate solution for a long time, and is not suitable for use in electrolytic copper environments. Although duplex stainless steel has certain corrosion resistance, it has high requirements for welding. The cathode plate, as an electrode, inevitably needs to be welded with related parts. The precipitated phase around the weld is likely to deteriorate the overall performance of the product, and the patent does not further discuss the processing of materials and the optimal composition combination.
[0006] Although the invention patent CN1399010A discloses that the cathode plate material is 1Cr18Ni9Ti, which to a certain extent overcomes the possibility of defects in the heat-affected zone around the weld, it only illustrates the advantages of the material compared with the traditional cathode plate material. Moreover, since 1Cr18Ni9Ti does not contain the Mo element, its corrosion resistance is slightly poor and its use environment is more restricted. It is also not suitable for use in the electrolytic copper environment.
[0007] Invention patent CN113897643A discloses a "stainless steel-copper-stainless steel" composite cathode plate material. Its main advantage is that it improves the current density of the cathode plate, but it does not improve the corrosion resistance of the material and solve the problem of copper layer peeling during the use of the cathode plate. In addition, the composite processing cost is high, which is not conducive to production enterprises to reduce production investment costs.
[0008] Invention patent CN102337564A also only discloses the shape, size and optimal surface roughness of the cathode plate, which can ensure that the cathode layer and the cathode plate have sufficient bonding, evenly distribute the bonding force, not easy to fall off, and ensure easy peeling after nickel production is completed. However, it does not explain how to improve the corrosion resistance of the cathode plate material and how to most economically realize the patented production method.
[0009] Invention patent CN1399010A discloses that a chemical oxidation or electrolytic oxidation treatment method is used to ensure that the cathode copper has good adhesion to the stainless steel cathode plate and is easy to peel off from the stainless steel. However, this method uses nitric acid or boric acid, which has high environmental requirements and is not suitable for general promotion.
[0010] Although the above-mentioned prior art has studied how to improve the corrosion resistance and copper attachment stability of the cathode plate from many aspects, it lacks research on the material itself and the processing method.
[0011] The cathode plate materials used in the existing electrolytic copper industry generally choose the 316L steel type or other mature and mass-produced stainless steel types that are circulated in the market. There are many studies on material selection and shape structure, but there are few studies on the optimization design of stainless steel composition in the electrolytic copper environment. Among the standard grades of stainless steel produced by many stainless steel plants, from the perspective of cost and benefit, steel plants generally only add alloy elements specified in the standards and retain impurity elements that cannot be completely removed to the upper limit specified in the standards in accordance with the requirements of the standards. There is no research and design on the composition of stainless steel for the electrolytic copper environment, which results in insufficient corrosion life of the cathode plate or excessive cost, and low production efficiency of electrolytic copper enterprises due to cathode plate problems. Summary of the invention
[0012] In order to overcome the above problems, the purpose of the present invention is to provide a stainless steel and a production method thereof and an electrolytic copper cathode plate. The electrolytic copper cathode plate made of stainless steel can improve the current density and corrosion resistance of the cathode plate, and has good copper attachment stability, can avoid the problem of insufficient copper adhesion or difficulty in peeling, has a long service life and low production cost.
[0013] In order to achieve the above object, the present invention provides a stainless steel, the chemical composition of which, in terms of weight percentage (the total weight of each element is 100%), comprises:
[0014] C: 0.01%-0.03%; Si≤1.0%; Mn≤2.0%; P≤0.045%; S≤0.002%; Cr: 16.5%-17.50%; Ni: 10.0%-10.5%; Mo: 2.0%-2.5%; N: ≤0.11%; Cu: 0.2%-0.7%; Co: 0.1%-0.5%, the balance is Fe and other inevitable impurity elements.
[0015] The stainless steel provided by the present invention can be used as the cathode plate stainless steel for electrolytic copper. Compared with the common 316L stainless steel commonly used for electrolytic copper pole plates, the present invention can not only improve the current density and current stability of the electrolytic copper cathode plate made of stainless steel by adding cobalt and copper elements to the stainless steel, but also greatly improve the corrosion resistance of the stainless steel in the electrolyte (such as sulfuric acid-copper sulfate solution).
[0016] The present invention has found that the cobalt element in stainless steel reduces the stability of austenite, causes the austenite isothermal transformation curve (C-curve) in the steel to shift to the left, and can improve the strength and wear resistance of stainless steel. The present invention can inhibit the growth of ferrite and austenite and promote the formation of martensite by adding an appropriate amount of cobalt, thereby improving the strength and hardness of stainless steel; and by adding cobalt elements, the steel can also be given hot hardness, improve the high temperature performance, oxidation resistance and corrosion resistance of the steel, and the cobalt element can be used as an important alloying element for superhard high-speed steel, hard alloy, cobalt-based heat-resistant alloy, magnetic steel or hard magnetic alloy. In addition, the cobalt element has a solid solution strengthening effect, which can further improve the performance of stainless steel.
[0017] In terms of cobalt content regulation, the present invention has found that excessive cobalt content in stainless steel may reduce processing performance: excessive cobalt content will increase the hardness of stainless steel, making it more difficult to cut and cold process, thereby reducing its processing performance. Moreover, excessive cobalt content may increase the brittleness of stainless steel, making it easy to crack or break when subjected to impact or pressure, thereby affecting its toughness and durability. By controlling the cobalt content in stainless steel, the present invention can avoid the reduction of stainless steel processing performance and mechanical properties caused by excessive cobalt while giving full play to the role of cobalt in enhancing and improving the structure and performance of stainless steel. In addition, the addition of cobalt can reduce the stacking fault energy of steel and promote the formation of twins, thereby improving the wear resistance of steel. The addition of an appropriate amount of cobalt (such as a cobalt content of 0.1%-0.5% or 0.2%-0.3% in steel) is beneficial to Fe 15 Cr 8 Ni 8 Co will form, but if there is too much cobalt, Fe 14 Cr 8 Ni 8 Co 2 The two compounds have different elastic moduli and have different effects on tissue properties.
[0018] The present invention has found that by adding copper to stainless steel, the stability of austenite in stainless steel can be improved, and the hardenability and hardenability can be improved. Adding a certain amount of copper to austenitic stainless steel can effectively improve the acid corrosion resistance, and can improve the corrosion resistance of austenitic stainless steel in reducing media and improve the toughness of steel. In addition, adding a certain amount of copper to steel, especially when used in combination with phosphorus, can improve the corrosion resistance of stainless steel to the atmosphere.
[0019] In terms of the regulation of copper content, the present invention finds that the copper content in stainless steel is greater than 0.35%, which can promote aging hardening. This is because the solubility of copper in α-iron varies greatly, reaching 3.5% at 830°C and dropping to 0.35% at 20°C. When the copper content in stainless steel is ≥0.2%, the surface selectively oxidizes during the heating process, causing iron to oxidize before copper, and the surface copper increases relatively to form a thin film, and then diffuses to form a copper-containing network. When the nickel element in the steel is high, the nickel element and copper can generate a copper-nickel solid solution with a higher melting point, which reduces the resistance of the passivation layer on the surface of the stainless steel and effectively increases the surface current density; when the copper content in the stainless steel is ≤0.7%, copper will dissolve in α-Fe, which prevents carbon from oxidizing. When the copper content in stainless steel is 0.5%, the rust prevention ability can be increased by 15 times. However, the present invention has found that when the copper content is high, the steel will become hot brittle, making hot forging and rolling difficult. For example, when the copper content in stainless steel reaches more than 0.7%, an inhomogeneous mixture will appear, which will increase the coercive force and hysteresis loss and make the copper material brittle. Therefore, the present invention can reduce the resistance of stainless steel, increase the surface current, avoid oxidation, and ensure that the stainless steel has good processing properties by controlling the copper content in stainless steel.
[0020] The functions and contents of the elements in the stainless steel of the present invention may be:
[0021] Carbon (C): C is an element that is beneficial to increasing the strength of stainless steel in terms of solid solution strengthening principle, and is also an austenite stabilizing element. However, excessive C will cause the Cr element, which is beneficial to corrosion resistance, to form carbides on the ferrite-austenite interface, reducing the content of Cr and other elements around the grains, and reducing the corrosion resistance of stainless steel. In some specific embodiments, the weight content of the C element in stainless steel can be controlled to be 0.01-0.03%, for example, 0.01%, 0.015%, 0.02%, 0.025%, 0.03% and other specific values, as well as a range with any two of the above specific values as endpoints.
[0022] Nitrogen (N): N is one of the elements that contributes most to the stabilization of the austenite phase in stainless steel, and increasing the N content can improve corrosion resistance and strength. However, too high a N content will reduce the processability of stainless steel, and too low a N content requires a corresponding reduction in Cr to ensure phase balance, and it also has an adverse effect on stabilizing phase balance and ensuring strength. In some specific embodiments, the weight content of the N element in stainless steel can be controlled to be ≤0.11%, that is, greater than 0 and less than or equal to 0.11%, such as 0.04%-0.11%, and can be specifically 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11% and other specific values and a range with any two of the above specific values as endpoints; it can be further controlled to be 0.04%-0.06%.
[0023] Chromium (Cr): Cr is an element necessary to ensure the corrosion resistance of stainless steel. Increasing the Cr content can improve the corrosion resistance of stainless steel, but too much Cr content will lead to the formation of too much ferrite in the stainless steel, and it is impossible to ensure that the stainless steel has sufficient tensile elongation. In some specific embodiments, the weight content of the Cr element in the stainless steel can be controlled to be 16.5%-17.5%, specifically 16.5%, 16.6%, 16.7%, 16.8%, 16.9%, 17.0%, 17.1%, 17.2%, 17.3%, 17.4%, 17.5% and other specific values and a range with any two of the above specific values as endpoints; it can be further controlled to be 16.6%-17.0%.
[0024] Manganese (Mn): Mn is a stabilizing element for the austenite phase. In some specific embodiments, the weight content of the Mn element in the stainless steel can be controlled to be ≤2.0%, that is, greater than 0 and less than or equal to 2.0%, and can be specifically 0.8%, 1.0%, 1.5%, 2.0%, and other specific values, and a range with any two of the above specific values as endpoints; further, it can be controlled to be 0.8%-2.0%.
[0025] Nickel (Ni): Ni, like Mn and N, is an austenite phase stabilizing element. Insufficient Ni content will reduce the corrosion resistance and processability of stainless steel. Controlling the Ni content within an appropriate range can ensure the stability of austenite and meet the needs of later welding processing of the cathode plate. In addition, in the actual production process, the nitrogen element in austenitic steel is very easy to precipitate, causing the steel to produce pores and become unusable. The present invention can avoid the above problems by partially replacing the nitrogen element with nickel. In some specific embodiments, the weight content of the Ni element in stainless steel can be controlled to be 10.1%-10.5%, specifically 10.1%, 10.2%, 10.3%, 10.4%, 10.5% and other specific values, as well as a range with any two of the above specific values as endpoints; further, it can be 10.1%-10.3%.
[0026] Molybdenum (Mo): Molybdenum in steel can improve hardenability and heat strength, prevent temper brittleness, increase remanence and coercivity, and corrosion resistance in certain media. In stainless acid-resistant steel, molybdenum can further improve corrosion resistance to resistant acids (such as formic acid, acetic acid, oxalic acid, etc.) as well as hydrogen peroxide, sulfuric acid, sulfurous acid, sulfates, acid dyes, bleaching powder solution, etc. In particular, the addition of molybdenum can prevent the pitting corrosion tendency caused by chloride ions. In some specific embodiments, the weight content of the Mo element in stainless steel can be controlled to be 2.0%-2.5%, specifically 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5% and other specific values and a range with any two of the above specific values as endpoints; it can be further controlled to be 2.0%-2.2%.
[0027] Cobalt (Co): Co element can improve the stability of austenite in stainless steel. A proper amount of cobalt can inhibit the growth of ferrite and austenite, improve the strength and wear resistance of stainless steel, and reduce the damage to the cathode plate during the stripping process when stripping the deposited copper on the cathode plate, effectively extending the service life of the cathode plate. In some specific embodiments, the weight content of the Co element in stainless steel can be controlled to be 0.1%-0.5%, specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.5% and other specific values, as well as a range with any two of the above specific values as endpoints; it can be further controlled to be 0.2%-0.3%.
[0028] Copper (Cu): Copper can improve the stability of austenite in stainless steel, improve hardenability and hardenability. Adding a certain amount of copper to austenitic stainless steel can effectively improve the acid corrosion resistance. Moreover, after the copper-rich phase is generated in the surface passivation film, the surface resistivity of the cathode plate can be greatly reduced, the current density can be increased, and the copper ions can be quickly deposited on the surface of the cathode plate during the use of the electrolytic copper cathode plate. In some specific embodiments, the weight content of the Cu element in stainless steel can be controlled to be 0.2%-0.7%, specifically 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.65%, 0.70% and other specific values and a range with any two of the above specific values as endpoints; it can be further controlled to be 0.35%-0.7%, and further controlled to be 0.4%-0.5%.
[0029] In some specific embodiments, the weight content of the Si element in the stainless steel can be controlled to be ≤1.0%, that is, greater than 0 and less than or equal to 1.0%, and can be specifically 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% and other specific values, as well as a range with any two of the above specific values as endpoints; it can be further controlled to be 0.3%-0.8%, and further can be 0.4%-0.8% or 0.3%-0.6%.
[0030] According to a specific embodiment of the present invention, the weight content of the P element in the stainless steel can be ≤0.045% (including the case where the content is 0), and specifically can be 0%, 0.005%, 0.010%, 0.015%, 0.020%, 0.025%, 0.030%, 0.035%, 0.040%, 0.045% and other specific values, as well as a range with any two of the above specific values as endpoints; further, the weight content of the P element in the stainless steel can be less than 350ppm.
[0031] According to a specific embodiment of the present invention, the weight content of the S element in the stainless steel can be ≤0.002% (including the case where the content is 0), and specifically can be 0%, 0.001%, 0.0011%, 0.0012%, 0.0013%, 0.0014%, 0.0015%, 0.0016%, 0.0017%, 0.0018%, 0.0019%, 0.002% and other specific values, and a range with any two of the above specific values as endpoints; further, the weight content of the S element in the stainless steel can be less than 20 ppm.
[0032] According to a specific embodiment of the present invention, the chemical composition of the stainless steel may further satisfy, by weight percentage: Cr: 16.6%-17.0%; Ni: 10.1%-10.3%; Mo: 2.0%-2.2%; Mn: 0.2%-2.0%; N: 0.04%-0.06%; Si: 0.3%-0.8%.
[0033] According to a specific embodiment of the present invention, the content of delta ferrite in the stainless steel is 3%-10%, for example, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% and other specific values and ranges with any two of the above specific values as endpoints. The delta ferrite in this content range can reduce the solidification cracks in the weld of austenitic stainless steel during welding; high temperature ferrite (delta ferrite) is beneficial to reduce the tendency of stress corrosion cracking in the solidification structure of the weld. Further, the ferrite content in the stainless steel can be 6%-8%.
[0034] In the present invention, the calculation formula of the delta ferrite content is:
[0035] δ={(Cr+Mo+1.5Si+0.5Nb+18) / [Ni+0.52Cu+30(C+N)+0.5Mn+36]+0.262}×161-161;
[0036] In the above formula, the element symbol represents the content of the element expressed in weight percentage (for example, when the Cr content is 17%, substitute 17%), and the unit of δ is %.
[0037] The present invention also provides a production method of the above stainless steel, which comprises sequentially performing billet smelting, slab heating, slab rolling, black coil annealing and pickling, cold rolling, cold rolled coil annealing and pickling, and roll leveling to obtain the stainless steel;
[0038] Wherein, the rolling force of the roll leveling machine is 100 tons-200 tons; the surface roughness Ra of the roll of the roll leveling machine is 1.0 μm-2.0 μm.
[0039] The production method provided by the present invention can be carried out in a cold-rolled stainless steel strip production device.
[0040] In the above production method, the steel billet smelting includes the operation of subjecting the raw materials to sequential smelting in an electric furnace, argon oxygen decarburization refining, and refining furnace, and then continuously casting them into slabs.
[0041] In the above production method, the slab heating includes heating in the preheating section, the heating section and the soaking section in sequence, and then hot rolling. The temperature of the preheating section can be 910-930°C, and the heating time of the preheating section can be 115-125min; the temperature of the heating section can be 1070-1100°C, and the heating time of the heating section can be 35-45min; the temperature of the soaking section can be 1200-1260°C, and the heating time of the soaking section can be 75-85min. The total heating time of the slab heating can be controlled to be 225-255min.
[0042] In the above production method, the slab rolling includes the process of sequentially rough rolling and finish rolling of the steel to obtain a hot-rolled black coil.
[0043] In the above production method, the black coil annealing and pickling includes subjecting the stainless steel black coil obtained by slab rolling to solid solution heat treatment in an annealing and pickling furnace (which may be a continuous annealing and pickling furnace), pickling the heat-treated product, and obtaining a hot-rolled white coil. The temperature of the solid solution heat treatment may be 1050-1100°C, such as 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, and other specific values, and a range with any two of the above specific values as endpoints; the time of the solid solution heat treatment may be 5min-6min.
[0044] In the above production method, the cold rolled coil annealing and pickling includes the operation of subjecting the cold rolled steel to high temperature solid solution annealing in an annealing and pickling furnace (which may be a continuous stainless steel annealing and pickling furnace). In the cold rolled coil annealing and pickling, the solid solution annealing temperature may be 1050-1080°C, for example, it may be 1050°C, 1055°C, 1060°C, 1065°C, 1070°C, 1075°C, 1080°C and other specific values and a range with any two of the above specific values as endpoints. The existing stainless steel production method usually adopts a low temperature annealing temperature, which cannot avoid the problem of stress release and deformation of the steel plate in the later stage. The annealing temperature above 1050°C adopted in the present invention is a complete solid solution annealing, which can completely eliminate residual stress and avoid deformation of the cathode plate after stress release during the later use and processing, resulting in short circuit.
[0045] In the above production method, in the cold rolled coil annealing and pickling, the solution annealing time can be 1.5-2 min, for example, it can be 1.5 min, 1.6 min, 1.7 min, 1.8 min, 1.9 min, 2 min and other specific values, as well as a range with any two of the above specific values as endpoints.
[0046] The surface roughness of 316L stainless steel products obtained by the existing 316L cold-rolled stainless steel strip production process is about Ra < 0.2μm. The key to the success of the stainless steel cathode plate lies in the stripping of the cathode copper. Good surface conditions and appropriate cathode copper adhesion should prevent the cathode copper from falling off from the plate surface by itself within the electrolysis cycle, and after reaching the electrolysis cycle, it is easy to strip from the plate surface with the help of machinery or manpower, while ensuring the good surface quality and physical specifications of the cathode copper. The ideal roughness range Ra of stainless steel for copper electrolysis cathode plates is 0.4μm-0.6μm. To meet this requirement, the existing technology mostly adopts surface sandblasting or grinding processes, resulting in increased production costs. The above-mentioned production method provided by the present invention can utilize existing equipment (such as cold-rolled stainless steel strip production equipment) to produce stainless steel strips with a roughness range Ra of 0.4μm-0.6μm by improving the process without increasing production costs, providing suitable stainless steel materials for downstream cathode plate manufacturers, thereby significantly reducing the manufacturing cost of cathode plates.
[0047] In the above production method, the roll leveling machine leveling includes the process of leveling the cold-rolled coil annealed and pickled steel strip in the roll leveling machine. The roll leveling machine applies rolling force to replicate the rough texture of the rough surface of the roll on the surface of the strip, thereby regulating the roughness of the strip surface. By combining the roll roughness of the leveling machine with the rolling force, the surface roughness of the steel strip can be accurately controlled. In the case of omitting the sandblasting process, a stainless steel product with a surface roughness of 0.4-0.6μm can be directly obtained, which saves the processing technology for adjusting the surface roughness of the steel strip in the later stage, greatly reduces the processing cost, and has good economic utilization value.
[0048] In a specific embodiment, the surface roughness Ra of the rolling mill roller can be 1.0-2.0μm, for example, specific values such as 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm, and a range with any two of the above specific values as endpoints; the rolling force applied by the leveling mill can be 100 tons-200 tons, specifically 100 tons, 110 tons, 120 tons, 130 tons, 140 tons, 150 tons, 160 tons, 170 tons, 180 tons, 190 tons, 200 tons, and a range with any two of the above specific values as endpoints, for example, 150 tons-200 tons.
[0049] In the above production method, the elongation of the flattened steel strip of the roll skinner is ≤1.0%.
[0050] In the above production method, the diameter of the roller of the roller leveling machine can be 800mm-820mm, for example, it can be specific values such as 800mm, 805mm, 810mm, 815mm, 820mm, and a range with any two of the above specific values as endpoints.
[0051] In some specific embodiments, when the flattening machine uses a relatively small pressure for flattening, the flatness of the steel strip may be slightly poor. In this regard, the above production method may further include performing tension straightening treatment on the flattened steel strip to ensure that the steel strip product is flat and has a good surface roughness. Specifically, when the flatness of the flattened steel strip is not ideal, for example, when the middle wave or side wave of the flattened steel strip is greater than or equal to 1 mm, a tension straightening treatment process may be performed.
[0052] The tension of the tension straightening treatment can be adjusted according to the flatness of the flattened steel strip. The minimum tension of the tension straightening treatment can meet the following conditions:
[0053] Minimum tension = 330N / mm × steel belt width × steel belt thickness;
[0054] Among them, the unit of minimum tension is N, the unit of steel strip width is mm, and the unit of steel strip thickness is mm.
[0055] In the above production method, the surface roughness Ra of the stainless steel produced by the production method is 0.4-0.6μm, which can meet the requirements of the copper electrolysis cathode plate for the surface roughness of stainless steel. The surface roughness of the stainless steel can be 0.4μm, 0.41μm, 0.42μm, 0.43μm, 0.44μm, 0.45μm, 0.46μm, 0.47μm, 0.48μm, 0.49μm, 0.5μm, 0.51μm, 0.52μm, 0.53μm, 0.54μm, 0.55μm, 0.56μm, 0.57μm, 0.58μm, 0.59μm, 0.6μm and other specific values, as well as ranges with any two of the above specific values as endpoints.
[0056] According to a specific embodiment of the present invention, the above production method may specifically include:
[0057] Billet smelting: smelting the raw materials and continuously casting them into slabs, the chemical composition of the slabs being consistent with the chemical composition of the stainless steel provided by the present invention;
[0058] Slab heating: The slab is heated in the preheating section, heating section and soaking section of the heating furnace in sequence, and after reaching the temperature, the slab is taken out for hot rolling;
[0059] Slab rolling: The hot rolled steel is rough rolled in a rough rolling mill for 5-7 passes, then finish rolled into hot rolled black coil and cooled to room temperature;
[0060] Black coil annealing, pickling and cold rolling: The black coil is solution heat treated in a continuous annealing and pickling furnace, and then pickled to obtain hot-rolled white coil;
[0061] Annealing and pickling of cold rolled coils: The hot rolled white coils are rolled to a certain thickness by a cold rolling mill and then put into a continuous annealing and pickling furnace for high temperature solution annealing;
[0062] Roller leveling machine leveling: the strip is fed into the roller leveling machine, the roller diameter of the leveling machine is 800mm-820mm, the surface roughness of the roller is 1-2μm, the strip is leveled with a rolling force of 100 tons-200 tons, and the elongation of the leveled steel strip is ≤1.0%;
[0063] When the middle wave or side wave of the flattened steel strip is greater than or equal to 1mm, tension straightening treatment is carried out: the steel strip is sent to the tension straightening machine for tension straightening, and the minimum tension used meets the following requirements: minimum tension = 330N / mm × steel strip width × steel strip thickness;
[0064] Cutting: The steel strip is cut to a fixed length according to product requirements to obtain stainless steel that can be used for electrolytic copper cathode plates. The surface roughness of the stainless steel is 0.4-0.6μm.
[0065] The present invention utilizes the effect of adding the above-mentioned copper and cobalt elements to improve the electrical properties, mechanical properties, corrosion resistance and processability of stainless steel, as well as the effect of the surface roughness of stainless steel on improving the copper adhesion stability. Taking into account the economy, processability and specific use environment design purposes of the material, after multiple laboratory tests, a reasonable component ratio and processing technology of stainless steel for electrolytic copper cathode plates are finally determined. The stainless steel product obtained through internal organization production has significantly improved corrosion resistance, current density uniformity and stability of the deposited copper layer when used as an electrolytic copper cathode plate compared to conventional 316L stainless steel.
[0066] The present invention also provides an electrolytic copper cathode plate, which is made of the above-mentioned stainless steel.
[0067] According to a specific embodiment of the present invention, the method for producing electrolytic cathode copper using the above-mentioned electrolytic copper cathode plate may include: pre-making crude copper (containing 99% copper) into a thick plate as an anode, a stainless steel plate as a cathode, and a mixture of sulfuric acid and copper sulfate as an electrolyte. The anode, cathode and electrolyte are placed in a large electrolytic cell. After direct current is passed, copper dissolves from the anode into copper ions and moves to the cathode. After reaching the cathode, electrons are obtained to precipitate pure copper (electrolytic copper). Other impurity elements in crude copper that are more active than copper will dissolve into ions along with copper. The potential difference is appropriately adjusted to prevent these ions from precipitating on the cathode. Impurities that are less active than copper, such as gold and silver, gradually deposit at the bottom of the electrolytic cell, and secondary recovery of by-products can be used for precious metal refining. The electrolytic copper produced in this way has a purity of more than 99.95%, and is an important raw material for making electronic products, precision instruments, power equipment, etc.
[0068] According to a specific embodiment of the present invention, during the cathode stripping process, the stainless steel cathode is subjected to a large separation force during the stripping process of the cathode copper, and inevitably undergoes a certain degree of deformation. The yield strength of the electrolytic copper cathode plate made of ordinary 316L stainless steel is 260-300MPa, while the yield strength of the electrolytic copper cathode plate made of stainless steel of the present invention can reach 330MPa-360MPa (for example, 330MPa, 335MPa, 340MPa, 345MPa, 350MPa, 355MPa, 360MPa and other specific values and a range with any two of the above specific values as endpoints), which improves the deformation capacity by more than 10% compared to ordinary 316L stainless steel, and reduces the maintenance cost of the cathode plate in the later stage.
[0069] According to a specific embodiment of the present invention, in the same electrolytic copper electrolyte environment, the cathode plate made of stainless steel of the present invention has a higher current density at the same voltage than the cathode plate made of ordinary 316L stainless steel. For example, the current density of the cathode plate made of ordinary 316L stainless steel is 270-320A / m 2 The current density of the electrolytic copper cathode plate made of stainless steel provided by the present invention can reach 350A / m 2 -450A / m 2 (For example, 350A / m 2 、360A / m 2 、370A / m 2 、380A / m 2 、390A / m 2 , 400A / m 2 、410A / m 2 、420A / m 2 、430A / m 2 , 44A / m 2 , 450A / m 2 The current density of the electrolytic copper cathode plate provided by the present invention is significantly increased compared with the existing cathode plate, which can effectively reduce the adverse effects of the workshop environment caused by the temperature rise of the electrolytic cell and the accelerated volatilization of the electrolyte while improving the cathode copper production efficiency.
[0070] According to a specific embodiment of the present invention, the surface roughness of the above-mentioned electrolytic copper cathode plate provided by the present invention can be 0.4-0.6μm, and the average value of the cathode copper bonding strength is about 0.1MPa, such as 0.09-0.11MPa. Under the condition of this bonding strength, the cathode copper will neither be peeled off prematurely nor be difficult to peel off. Compared with the cathode plate made of ordinary 316L stainless steel used on the market, the cathode plate product provided by the present invention does not need mechanical polishing or sandblasting to make the product surface roughness better, saving a lot of manpower, material resources and costs.
[0071] In some specific embodiments, the copper electrolytic refining process is carried out under the conditions of a highly corrosive medium (e.g., a sulfuric acid solution with a concentration of about 170 g / L) and a relatively high temperature (e.g., above 60°C). In addition to high-concentration sulfuric acid in the electrolyte, a small amount of hydrochloric acid is added to improve the surface quality of the cathode copper, but the presence of chloride ions increases the pitting tendency of stainless steel. The corrosion resistance in the electrolyte is an important factor in whether the stainless steel cathode plate can be used for a long time and in measuring the service life of the cathode plate. In the present invention, by adding copper and cobalt elements to stainless steel, the cathode plate made of the stainless steel has a significantly improved corrosion resistance in the electrolytic copper electrolyte relative to the ordinary 316L cathode plate used on the market.
[0072] The beneficial effects of the present invention include:
[0073] 1. The present invention, from the perspective of the combination of raw material chemical components and the innovation of production methods, invents a new type of stainless steel for cathode plates of electrolytic copper and its industrialized production method, which is of great help to improve the service life of cathode plates used in the current electrolytic copper industry, reduce processing costs, and improve production stability. It not only successfully solves the problems of cathode plate corrosion and insufficient copper adhesion or difficulty in peeling during the electrolytic production of cathode copper, but also greatly reduces the production cost of stainless steel cathode plates, and realizes the industrialized production of stainless steel cathode plates.
[0074] Specifically, the present invention aims at the use environment of electrolytic copper, through a new design of the stainless steel composition, adding a certain amount of necessary elements, and matching a newly designed processing technology, ultimately solving the corrosion and abnormal peeling problems of cathode plates currently used in the electrolytic copper industry within a limited cost range, and realizing industrial mass production of a new cathode plate.
[0075] The production process provided by the present invention can be based on the original stainless steel production process, using existing equipment, adjusting process parameters by design, and producing stainless steel for cathode plates that is more suitable for electrolytic copper environments without increasing equipment investment or increasing costs.
[0076] 2. Compared with the common 316L cathode plates currently used in the market, the stainless steel products provided by the present invention have a significantly higher current density under the same voltage in the electrolytic copper electrolyte environment. While improving the cathode copper production efficiency, it effectively reduces the adverse effects of the workshop environment caused by the temperature rise of the electrolytic cell and the accelerated volatilization of the electrolyte.
[0077] In view of the problem that the stainless steel cathode is deformed to a certain extent due to the large separation force during the process of stripping the cathode copper, the yield strength of the stainless steel material provided by the present invention is significantly improved compared with the ordinary 316L stainless steel, and the deformation resistance is improved, which saves the company's later maintenance costs for the cathode plate;
[0078] The stainless steel of the present invention has good copper adhesion stability, and will neither cause premature peeling of cathode copper nor difficulty in peeling. Compared with the common 316L cathode plate used on the market, the product of the present invention does not need mechanical polishing or sandblasting, thus saving a lot of manpower and material resources.
[0079] The stainless steel product of the present invention has significantly improved corrosion resistance compared with ordinary 316L stainless steel by adding copper and cobalt elements, and can avoid pitting corrosion of stainless steel in electrolyte containing chloride ions, thereby improving the corrosion resistance and service life of the cathode plate in the copper electrolytic refining environment of high temperature and high corrosive medium.
[0080] 3. The stainless steel and its production method provided by the present invention successfully solve the problem that the stainless steel cathode plate is difficult to resist corrosion from dilute sulfuric acid in the electrolytic copper environment without increasing or reducing the cost, and at the same time increase the service life of the cathode plate, which has a great promoting effect on reducing production costs and improving production efficiency for downstream enterprises. BRIEF DESCRIPTION OF THE DRAWINGS
[0081] Figure 1 The error bars are the pitting potentials of the stainless steels of Example 1, Comparative Example 1, and Comparative Example 2.
[0082] Figure 2 The anodic polarization curves of the stainless steel of Example 1, Comparative Example 1 and Comparative Example 2 are shown. DETAILED DESCRIPTION
[0083] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0084] Example 1
[0085] This embodiment provides a stainless steel, and the chemical composition of the stainless steel includes, by weight percentage:
[0086] C: 0.017%; Si: 0.45%; Mn: 1.29%; P: 0.02%; S: 0.0013%; Cr: 16.65%; Ni: 10.2%; Mo: 2.02%; N: 0.047%, Cu: 0.41%; Co: 0.2%; the remainder is Fe and unavoidable impurity elements. The sum of the weights of the various components is 100%.
[0087] The present invention also provides a method for producing stainless steel, the method comprising:
[0088] 1. Billet smelting:
[0089] After smelting in EAF (electric furnace) + AOD (argon oxygen decarburization refining) + LT (refining furnace), it is continuously cast into slabs by a continuous casting machine;
[0090] Among them, the chemical composition mass percentage of the stainless steel slab is: C: 0.017%; Si: 0.45%; Mn: 1.29%; P: 0.02%; S: 0.0013%; Cr: 16.65%; Ni: 10.2%; Mo: 2.02%; N: 0.047%, Cu: 0.41%; Co: 0.2%; the remainder is Fe and unavoidable impurity elements; the sum of the weights of each element is 100%.
[0091] 2. Slab heating:
[0092] The slab is heated in a walking beam heating furnace, and the heating temperature is controlled according to the following requirements: preheating section 920°C, heating 120min; heating section: 1070-1100°C, heating 40min; soaking section: 1200-1260°C, heating 80min; the total heating time for the slab is 240 minutes, and after reaching the temperature, the slab is taken out for hot rolling.
[0093] 3. Rolling of slab:
[0094] The hot rolled steel is rough rolled for 5-7 times in a stainless steel rough rolling mill, and the plate and strip enter the furnace coil mill for finishing rolling to be a hot rolled black coil with a thickness of 5.0 mm. After laminar cooling, the coil is placed in a cooling yard for air cooling to room temperature.
[0095] 4. Annealing and pickling of black coil:
[0096] The stainless steel black coil is passed into a continuous annealing pickling furnace for solution heat treatment at a temperature of 1050-1100°C and a time of 5-6 minutes. The product after heat treatment is pickled on a pickling line, and the pickled stainless steel black coil becomes a hot-rolled white coil.
[0097] 5. Cold rolling, cold rolled coil annealing and pickling, roll leveling machine leveling, tension straightening treatment:
[0098] After the hot-rolled white coil is rolled to the required thickness by the cold rolling mill, it is sent to the continuous stainless steel annealing and pickling furnace. After high-temperature solution annealing at 1050℃ for 2 minutes, it enters the leveling machine with a roller roughness Ra of 1.5μm. The diameter of the leveling machine roller is 820mm. A 100-ton rolling force is used for one pass of leveling. The elongation of the leveled steel strip is ≤1.0%; when the middle wave or side wave of the leveled steel strip is greater than or equal to 1mm, tension straightening treatment is carried out: the steel strip is sent to the tension straightening machine, the tension is set according to the flatness of the strip, and one pass of tension straightening is carried out.
[0099] During tension straightening, the minimum tension is:
[0100] Minimum tension = 330N / mm × steel belt width × steel belt thickness;
[0101] The unit of minimum tension is N, and the unit of steel strip width and steel strip thickness is mm.
[0102] 6. According to product requirements, the tension-straightened steel strip is cut to a fixed length to obtain a stainless steel plate for an electrolytic copper cathode plate. At this time, the surface roughness Ra of the steel strip is measured to be 0.55 μm.
[0103] Example 2
[0104] This embodiment provides a stainless steel, and the chemical composition of the stainless steel includes, by weight percentage:
[0105] C: 0.024%; Si: 0.53%; Mn: 1.08%; P: 0.023%; S: 0.0011%; Cr: 17.08%; Ni: 10.11%; Mo: 2.08%; N: 0.043%, Cu: 0.5%; Co: 0.3%, the remainder is Fe and inevitable impurity elements. The sum of the weights of the various components is 100%.
[0106] This embodiment also provides a method for producing stainless steel, the method comprising:
[0107] 1. Smelting of steel billet:
[0108] After smelting in EAF (electric furnace) + AOD (argon oxygen decarburization refining) + LT (refining furnace), it is continuously cast into slabs by a continuous casting machine;
[0109] Among them, the chemical composition weight percentage of the stainless steel slab is: C: 0.024%; Si: 0.53%; Mn: 1.08%; P: 0.023%; S: 0.0011%; Cr: 17.08%; Ni: 10.11%; Mo: 2.08%; N: 0.043%, Cu: 0.5%; Co: 0.3%, the remainder is Fe and unavoidable impurity elements; the sum of the weights of each element is 100%.
[0110] 2. Slab heating:
[0111] The slab is heated in a walking beam heating furnace, and the heating temperature is controlled according to the following requirements: preheating section 920°C, heating 120min; heating section: 1070-1100°C, heating 40min; soaking section: 1200-1260°C, heating 80min; the total heating time for the slab is 240 minutes, and after reaching the temperature, the slab is taken out for hot rolling.
[0112] 3. Rolling of slab:
[0113] After 5-7 passes of rough rolling of the hot rolled material in the stainless steel rough rolling mill, the plate and strip enter the furnace coil mill for finishing rolling to be hot rolled black coil with a thickness of 4.0 mm. After laminar cooling, the coil is placed in the cooling yard for air cooling to room temperature.
[0114] 4. Annealing and pickling of black coil:
[0115] The stainless steel black coil is passed into a continuous annealing pickling furnace for solution heat treatment at a temperature of 1050-1100°C and a time of 5-6 minutes. The product after heat treatment is pickled on a pickling line, and the stainless steel black coil after pickling becomes a hot-rolled white coil.
[0116] 5. Cold rolling, cold rolled coil annealing and pickling, roll leveling machine leveling:
[0117] After the hot-rolled white coil is rolled to the required thickness by the cold rolling mill, it is sent to the continuous stainless steel annealing and pickling furnace. After high-temperature solution annealing at 1080℃ for 1.5 minutes, it enters the leveling machine with a roll roughness Ra of 1.0μm. The diameter of the leveling machine roll is 800mm. The rolling force of 150 tons is used for leveling once. The elongation of the leveled steel strip is ≤1.0%; the strip has good flatness, and when the middle wave and edge wave are less than 1mm, it can be directly cut to a fixed length to obtain a stainless steel plate for electrolytic copper cathode plate. The surface roughness Ra of the steel strip is measured to be 0.6μm.
[0118] The delta ferrite content in the stainless steel of Example 1 and Example 2 is calculated as follows:
[0119] δ={(Cr+Mo+1.5Si+0.5Nb+18) / [Ni+0.52Cu+30(C+N)+0.5Mn+36]+0.262}×161-161;
[0120] The unit of δ is %, and the element symbol represents the content of the element in weight percentage.
[0121] According to calculation, the weight content of delta ferrite in the stainless steel of Example 1 is 3.94%, and the weight content of delta ferrite in the stainless steel of Example 2 is 6.10%.
[0122] Comparative Example 1, Comparative Example 2
[0123] The production methods of the stainless steel of Comparative Examples 1 and 2 are similar to the production method of Example 1, except that the chemical composition of the steel billets is different and the rolling force of the leveler of Comparative Examples 1 and 2 is 300 tons.
[0124] The stainless steel of Comparative Example 1 is named Comparative Sample 1, and the stainless steel of Comparative Example 2 is named Comparative Sample 2. The surface roughness of the stainless steel of Comparative Example 1 and Comparative Example 2 is 0.1-0.2 μm.
[0125] The chemical compositions of the steel billets of Comparative Examples 1 and 2 are shown in Table 1. The units of the values other than the PREN values in Table 1 are %. The samples "1#" and "2#" in Table 1 are existing 316L stainless steel products, which are used to reflect the composition difference between the stainless steel of the present invention and the existing ordinary 316L stainless steel.
[0126] Table 1
[0127] Classification 1# 2# Comparison sample 1 Comparison sample 2 Example 1 Example 2 C 0.016 0.023 0.012 0.019 0.017 0.024 Si 0.47 0.53 0.75 0.58 0.45 0.53 Mn 1.37 0.92 0.89 1.16 1.29 1.08 P 0.0244 0.0327 0.0313 0.0304 0.02 0.023 S 0.002 0.005 0.005 0.002 0.0013 0.0011 Cr 16.1 16.29 16.54 16.5 16.65 17.08 Ni 10.15 10.5 10.11 12.16 10.2 10.11 Mo 2.07 2.06 2.02 2.04 2.02 2.08 Cu 0.02 0.11 0.06 0.02 0.41 0.5 N 0.0343 0.0403 0.0117 0.0126 0.047 0.043 Co 0 0 0.01 0.01 0.2 0.3 PREN 23.48 23.73 23.39 23.43 24.07 24.63 Delta ferrite content 3.96 3.44 9.46 2.37 3.94 6.1
[0128] According to GB / T1954-2008 "Method for measuring the ferrite content of chromium-nickel austenitic stainless steel welds", the ferrite content of the ingots of each sample in Table 1 was checked, which was basically consistent with the calculated results in Table 1.
[0129] The PREN in Table 1 is the pitting resistance equivalent, which is used to indicate the corrosion resistance of stainless steel. The calculation formula of PREN is:
[0130] PREN=Cr+3.3Mo+16N;
[0131] The symbol of each element represents the content of the element in weight percentage (for example, if the Cr content is 16.1%, substitute 16.1), and PREN is dimensionless.
[0132] The performance test of the stainless steel of Example 1 and Example 2 was carried out, and the results were as follows:
[0133] According to GB / T 228.1-2021 "Tensile Test of Metal Materials" standard, the yield strength of the stainless steel in Example 1 was measured to be 335 MPa, and the yield strength of the stainless steel in Example 2 was measured to be 342 MPa.
[0134] According to GB / T 351-2019 "Method for measuring resistivity of metallic materials", the current density of the stainless steel in Example 1 was measured to be 388A / m under the same voltage test conditions. 2 The current density of the stainless steel in Example 2 is 379 A / m 2 .
[0135] According to the experimental method of putting the embodiment and the comparative sample into the copper electrolytic cell of the same size for electrolysis for 120 hours, then welding the tie rods on the surface of the cathode copper of the stainless steel, bonding the tie rods and the cathode copper with epoxy resin, curing at a temperature of 100°C to achieve the maximum bonding strength of the epoxy resin, and then gradually pressurizing with a tensile testing machine, using the tensile force just separated from the cathode copper and the stainless steel cathode plate converted to the tensile force per unit area as the bonding strength, the copper bonding strength of the stainless steel of embodiment 1 is measured to be 0.09MPa, the copper bonding strength of the stainless steel of embodiment 2 is 0.11MPa, and the copper bonding strength of the comparative sample 1 is 0.03MPa. It can be seen that the stainless steel of embodiments 1-2 meets the relevant optimal bonding strength requirements.
[0136] According to GB / T 4334.6-2015 "5% sulfuric acid corrosion test method for stainless steel", the test conditions are immersion in 5% sulfuric acid solution for 48 days, the test temperature is 20°C, and the corrosion rate of the stainless steel in Example 1 is 0.361mm / d, and the corrosion rate of the stainless steel in Example 2 is 0.373mm / d. In contrast, the corrosion rate of ordinary 316L stainless steel is 0.439mm / d. It can be seen that the corrosion resistance of the stainless steel in the embodiment is improved by 17%-22% compared with the corrosion resistance of ordinary 316L stainless steel.
[0137] According to GB / T 17899-2023 "Corrosion of Metals and Alloys - Potentiodynamic Measurement of the Pitting Potential of Stainless Steel in Sodium Chloride Solution", the stainless steels of Example 1, Comparative Example 1 and Comparative Example 2 were tested for corrosion resistance and pitting corrosion resistance. Figure 1 : is the error bar of the pitting potential of the stainless steel of Example 1, Comparative Example 1 and Comparative Example 2, Figure 2 : is the anodic polarization curve of the stainless steel of Example 1, Comparative Example 1 and Comparative Example 2. Figure 1 , Figure 2 It can be seen that the pitting corrosion potential of the stainless steel in Example 1 is higher than that of the stainless steel in Comparative Example 1 and Comparative Example 2, indicating that the corrosion resistance and pitting corrosion resistance of the stainless steel in Example 1 are significantly better than those of the stainless steel in Comparative Example 1 and Comparative Example 2. The above results prove that by adding cobalt and copper to stainless steel and controlling the content of the two, the corrosion resistance and pitting corrosion resistance of stainless steel can be effectively improved.
[0138] It can be seen from the above results that the stainless steel provided by the present invention can be used to manufacture electrolytic copper cathode plates. The stainless steel can improve the current density and corrosion resistance (especially the corrosion resistance to acidic electrolyte) of the electrolytic copper cathode plate and improve the processability. The production method of the above stainless steel provided by the present invention can improve the surface roughness and copper adhesion stability of the stainless steel by improving the component ratio and process, and avoid the problem of insufficient copper adhesion or difficulty in peeling, and the service life is significantly increased without increasing the production cost by using existing equipment.
[0139] The present invention is not limited to the described embodiments. Those skilled in the art may make some modifications or changes without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the scope defined in the claims.
Claims
1. A stainless steel, wherein the chemical composition of the stainless steel comprises, by weight percentage: C: 0.01%-0.03%; Si≤1.0%; Mn≤2.0%; P≤0.045%; S≤0.002%; Cr: 16.5%-17.50%; Ni: 10.0%-10.5%; Mo: 2.0%-2.5%; N: ≤0.11%; Cu: 0.2%-0.7%; Co: 0.1%-0.5%, the balance being Fe and other inevitable impurity elements.
2. The stainless steel according to claim 1, wherein: The weight content of Cu in the stainless steel is 0.4%-0.5%; And / or, the weight content of Co in the stainless steel is 0.2%-0.3%.
3. The stainless steel according to claim 1 or 2, wherein: The chemical composition of the stainless steel also satisfies one or a combination of two or more of the following conditions: The weight content of Cr in the stainless steel is 16.6%-17.0%; The weight content of Ni in the stainless steel is 10.1%-10.3%; The weight content of Mo in the stainless steel is 2.0%-2.2%; The weight content of Mn in the stainless steel is 0.8%-2.0%; The weight content of N in the stainless steel is 0.04%-0.06%; The weight content of Si in the stainless steel is 0.3%-0.8%; Preferably, the chemical composition of the stainless steel further satisfies one or a combination of two or more of the following conditions: the weight content of the P element in the stainless steel is less than 350 ppm; the weight content of the S element in the stainless steel is less than 20 ppm.
4. The stainless steel according to claim 1, wherein: The stainless steel contains delta ferrite, and the content of delta ferrite in the stainless steel is 3%-10%; The calculation formula of the content of delta ferrite is: δ={(Cr+Mo+1.5Si+0.5Nb+18) / [Ni+0.52Cu+30(C+N)+0.5Mn+36]+0.262}×161-161; The unit of δ is %, and the element symbol indicates the content of the element in weight percentage; Preferably, the ferrite content in the stainless steel is 6%-8%.
5. The method for producing stainless steel according to any one of claims 1 to 4, comprising the steps of smelting billets, heating slabs, rolling slabs, annealing and pickling of black coils, cold rolling, annealing and pickling of cold rolled coils, and leveling by a roller leveler, to obtain the stainless steel; in, The rolling force of the roller skin-pass mill is 100 tons to 200 tons; The surface roughness Ra of the roller of the roller leveler is 1.0 μm-2.0 μm.
6. The production method according to claim 5, wherein: The roller diameter of the roller leveler is 800mm-820mm; The elongation of the flattened steel strip of the roll skin-passing machine is ≤1.0%.
7. The production method according to claim 6, wherein: The production method further comprises performing tension straightening treatment on the flattened steel strip, wherein the minimum tension of the tension straightening treatment is: Minimum tension = 330N / mm × steel belt width × steel belt thickness; Among them, the unit of minimum tension is N, the unit of steel strip width is mm, and the unit of steel strip thickness is mm.
8. The production method according to claim 6, wherein: In the cold rolled coil annealing and pickling, the solution annealing temperature used is 1050-1080°C.
9. The production method according to claim 6, wherein: The surface roughness Ra of the stainless steel produced by the production method is 0.4-0.6 μm.
10. An electrolytic copper cathode plate, made of the stainless steel according to any one of claims 1 to 4; Preferably, the yield strength of the electrolytic copper cathode plate is 330MPa-360MPa; Preferably, the current density of the electrolytic copper cathode plate is 350A / m 2 -450A / m 2 .
Citation Information
Patent Citations
Stainless steel electrolytic plates
CN101166850A
Electrodeposition electrolytic nickel negative plate
CN102337564A
Sandwich composite metal electrolysis and deposition cathode plate
CN113897643A
Making process of durable stainless steel cathode plate for copper electrolyzing refining
CN1399010A